2016
DOI: 10.2147/ijn.s105274
|View full text |Cite
|
Sign up to set email alerts
|

Pericyte-targeting drug delivery and tissue engineering

Abstract: Pericytes are contractile mural cells that wrap around the endothelial cells of capillaries and venules. Depending on the triggers by cellular signals, pericytes have specific functionality in tumor microenvironments, properties of potent stem cells, and plasticity in cellular pathology. These features of pericytes can be activated for the promotion or reduction of angiogenesis. Frontier studies have exploited pericyte-targeting drug delivery, using pericyte-specific peptides, small molecules, and DNA in tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…One recent study demonstrated successful peptide-conjugated nanoparticle delivery of the anticancer drug docetaxel to peripheral pericytes in rats with neuroblastoma (Guan et al, 2014), while peptide-conjugated liposomal nanoparticles have also been used to effectively target pericytes and deliver the anticancer drug doxorubicin in mice with lung melanoma (Loi et al, 2010). Nanoparticle formulation with pericyte-binding peptide sequences is possible (Kang and Shin, 2016) but it has not yet been trialed in the brain. The delivery of pericyte-targeted drugs through nanoparticles could provide a novel therapeutic avenue for the treatment of many neurovascular diseases.…”
Section: Future Directionsmentioning
confidence: 99%
“…One recent study demonstrated successful peptide-conjugated nanoparticle delivery of the anticancer drug docetaxel to peripheral pericytes in rats with neuroblastoma (Guan et al, 2014), while peptide-conjugated liposomal nanoparticles have also been used to effectively target pericytes and deliver the anticancer drug doxorubicin in mice with lung melanoma (Loi et al, 2010). Nanoparticle formulation with pericyte-binding peptide sequences is possible (Kang and Shin, 2016) but it has not yet been trialed in the brain. The delivery of pericyte-targeted drugs through nanoparticles could provide a novel therapeutic avenue for the treatment of many neurovascular diseases.…”
Section: Future Directionsmentioning
confidence: 99%
“…Literature cites that they strengthen the blood vessel barrier in co-ordination with endothelial cells or other blood components, thereby preventing vascular leakage. Besides this, they are also known as metastatic stimulators and contribute in accumulation of cancer stem cells within tumor microenvironment (Gerhardt and Betsholtz, 2003 ; Kang and Shin, 2016 ; Ferland-McCollough et al, 2017 ).…”
Section: Understanding the Challenges And Opportunities Presented By mentioning
confidence: 99%
“…Targeting pericytes through nanotechnology could become a novel treatment strategy for stroke, and this is made possible through the formulation of nanoparticles with pericyte-binding peptide sequences. 164 However, these pericyte-targeting nanoparticles have yet to be trialed in the brain.…”
Section: Other Areas Of Interest For Strokementioning
confidence: 99%